2020
DOI: 10.4103/atm.atm_147_20
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B as antiviral drug: Possible efficacy against COVID-19

Abstract: Since its discovery, amphotericin B (AmB) is still one of the most common first-line choices in treatment pulmonary mycoses for over seventh decades from discovery. AmB which is belonged to the polyene group has a wide spectrum in vitro and in vivo antimicrobial activity against fungi and parasites, resistance to AmB is rare despite extensive use. Recently, some studies focused on the potential antimicrobial action of AmB against some enveloped viruses such as huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Besides, some studies have introduced already known antifungal agents as antiviral drugs for COVID-19 treatment. Al-Khikani (2020) suggested amphotericin B, an antifungal drug, as a potential antiviral agent against enveloped viruses. Terbinafine, another antifungal agent with the same mechanism of action with tolnaftate ( https://go.drugbank.com/drugs/DB00857, 2020 ), was also reported as a COVID-19 therapeutic option in some available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies have introduced already known antifungal agents as antiviral drugs for COVID-19 treatment. Al-Khikani (2020) suggested amphotericin B, an antifungal drug, as a potential antiviral agent against enveloped viruses. Terbinafine, another antifungal agent with the same mechanism of action with tolnaftate ( https://go.drugbank.com/drugs/DB00857, 2020 ), was also reported as a COVID-19 therapeutic option in some available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Natamycin is used to treat blepharitis (Fungal infection of eye), fungal conjunctivitis, and fungal keratitis [ 317 ]. In addition to polyenes’ use as antimycotics and antiparasitics, experimental trials of other therapeutic applications have been reported [ 318 , 319 ].…”
Section: Clinical Use Of Polyenesmentioning
confidence: 99%
“…Recently, the immunomodulation of AmB has been suggested for action against COVID‐19, as it is able to act on the cholesterol‐like structure of the viral envelope. The removal of the cholesterol‐like envelope reduces the viral load on treatment with AmB [58]. AmB can also weaken the attachment and uptake of enterovirus by host cells [59].…”
Section: Antifungal Drugsmentioning
confidence: 99%